HEPATOPROTECTIVE EFFECT OF WHOLE PLANT EXTRACT FRACTIONS OF MARSILEA MINUTA - balne, divya; Pallerla, Praneetha; Vanapatla, Swaroopa Rani; Bobbala, Ravi Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective: The objective of the study is to separate and identify the most effective hapatoprotective fraction of methanolic extract of Marsilea minuta (MMME) by fractionating and evaluating its fractions for hapatoprotective activity in three mechanistically devised models viz., CCl4, paracetamol and ethanol induced liver damage in rats. Methods: Acute toxicity study was carried out to the fractions according to the organization for economic corporation development (OECD)-420 guidelines. Liver damage was induced in different groups of rats by administering 1:1v/v CCl4 in olive oil 1ml/kg.b.w.p.o, 3g/kg.b.w.p.o paracetamol and 5g/kg.b.w.p.o ethanol and the effect of fractions were tested for hepatoprotective potential by evaluating serum biochemical parameters, histology of liver of rats and the most effective bioactive fraction was screened for its effect on hepatic microsomal drug metabolizing enzymes (MDMA) and prothrombin time (PT). It was also tested for its antioxidant properties by DPPH method, lipid peroxidation method and for detection of different classes of chemicals present in it. Results: Pretreatment with fractions (toluene, 1-butanol, aqueous at 50, 100mg/kg.b.w) significantly reversed the changes in serum biochemical parameters and histology of liver caused by the three hepatotoxins namely CCl4, paracetamol and ethanol indicating their hepatoprotective activity. The hepatoprotective activity of butanol fraction of MMME (BF-MMME) was well supported in MDMA, PT and DPPH studies. Conclusion: Â All the fractions of MMME exhibited significant hepatoprotective activity; out of all the fractions BF-MMME (50mg/kg) was identified to be most effective hepatoprotective fraction. Â  Keywords: Marsilea minuta, Hepatoprotective activity, CCl4, Paracetamol, Ethanol, Silibinin, DPPH.